ANALISIS PENGARUH KOMPETENSI SDM DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA SEKRETARIAT DAERAH KABUPATEN PINRANG - ANITHA NITA TAHIR; Mashur Razak; Saripuddin D (Nobel Management Review, 2020)
The purpose of this study was to analyze the effect of HR potential and leadership style on employee performance through job satisfaction at the Pinrang district secretariat. This research approach is a quantitative descriptive approach. A total of 58 respondents were taken as samples in this study. The instrument used to test the appropriateness of a question in the questionnaire is a validity test and a reliability test. For the method of data analysis used in this study is the classic assumption test which is strengthened by the normality test and multicorrelation test and in testing the hypothesis includes multiple linear regression analysis, t test and test model determination (F and R2 tests) using SPSS 16.0. The results of the study are known that the Direct Effect of Human Compotence on Job Satisfaction is 0.240 or 24.0% with a t value> t table value of 2.164> 2.004. The direct influence of leadership style on job satisfaction is 0.509 or 50.9% with a t value of 5.573> 2.004. The direct influence of leadership style on performance is 0.565 or 56.5% with a t value of 4.871> 2.004. The direct effect of HR Competence on Performance is 0.385 or 38.5% with a t value of 2.737> 2.004. The direct effect of job satisfaction on performance is 0.722 or 72.2% with a t value of 5.305> 2.004. The indirect effect of HR competence and leadership style on performance through employee job satisfaction is 0.613 or 61.3%. The indirect influence of leadership style on performance through job satisfaction is 0.626 or 62.6% with a t value of 4.923> 2.004.